Boosting strawberry yield and fruit sweetness with humic substances and biofertilizer in soilless cocopeat-based culture - Reginawanti Hindersah; Ratna Ayu Permata Aini; Mieke Rochimi Setiawati; Tualar Simarmata; Diky Indrawibawa; Masako Akutsu (Universitas Lancang Kuning, 2023)
Farmers usually apply more chemical fertilizers to enhance the yield of strawberries in soilless culture. Humic substances and biofertilizers are now considered essential nutrient sources in sustainable agriculture. The objective of the greenhouse experiment was to observe the effect of humic and fulvic acid (humic substances), and biofertilizer on root growth, nitrogen (N) and phosphor (P) of the growing media, populations of N-fixing and P-solubilizing bacteria in the root zone, and yield of strawberry grown in the cocopeat-based substrate. The experiment was set up in a randomized block design consisting of seven treatments and four replications. The treatments included humic acid, fulvic acid, and biofertilizer in single or combined applications. All data were subjected to analysis of variance and followed by Duncan's Multiple Range Test with p<0.05. All treatments received 50% of the recommended dose of NPK fertilizer. The results showed that all treatments did not affect root length and dry weight. Mixed application of humic substances and biofertilizer together with NPK fertilizer increased total N and P as well as the population of N-fixing bacteria in the growth substrate. Still, P-solubilizing bacteria did not grow in the cocopeat-based substrate. Moreover, mixing humic substances and biofertilizer increased strawberries' fruit yield and sweetness levels.